Pengaruh Kepemimpinan Kepala Sekolah, Kompetensi Guru dan Etos Kerja Guru terhadap Prestasi Belajar Siswa: (Sekolah Menengah Pertama Negeri Tangerang Selatan di Kecamatan Pamulang) - Henni Marlinah (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2019)
The purposse of this research is to know the influence principal’s leadership, teacher competence and work ethic of teacher toword on student’s learning achievement at SMPN south tangerang city in pamulang district. This hypothesis is made to know that there are positive and significant influence both partially and simultaneously between independent variables with dependent variable. The method used in this research is quantitative. While the sample in this research are the all teachers at SMPN south tangerang city in pamulang district which amounted to 140 people using Slovin sampling technique to find samples that will be used to random respndents. The results of these research show that the effected parcially between leadership of the principal on the positive student learning achievement of thitung 2,242 at a significant level of 0,027. There is partial influence between the competence of teachers to student achievement of thitung 2,428 at a significant level of 0,016. There is patial influence between work athic of teacher to positive student learning achievement equal to thitung 2,262 at a significant level 0,025. And simultaneous relationships occur between the pricipal’s leadership, teacher competence and work ethic of teachers on positive student learning achievement of fhitung 3,741 with a significant level of 0,013. So, this hypothesis can be concluded there is positive and significant influence between principal leadership, teacher competence and work ethic of teacher to student achievment both partially and simultaneously.